Atmospheric diffusion study of surface leakage from CO2 enhanced oil recovery with carbon capture and storage based on flux monitoring-CFD simulation - QU Changqing, LIN Qianguo (Youqicang pingjia yu kaifa)
CO2 enhanced oil recovery（EOR） with carbon capture and storage（CCS） projects offer dual benefits of increasing oil recovery and CO2 storage, making it one of the most economically viable carbon sequestration methods nowadays. However, EOR-CCS projects typically involve multiple well sites, and the high risk of CO2 leakage from wellbores poses significant safety and environmental challenges over large areas. To address the limitations of previous atmospheric diffusion studies based on point-source leakage at well sites, a new method for studying surface CO2 leakage and atmospheric diffusion in EOR-CCS projects based on area-source flux monitoring at well sites was developed. A case study of an oilfield in East China, based on scenario analysis, demonstrated that CO2 leakage flux monitoring using the eddy covariance method could provide accurate data on area-source leakage fluxes for entire well sites, enabling large-scale computational fluid dynamics（CFD） simulations. Multi-well-site CFD diffusion simulations effectively captured the impact of complex regional topography and multiple well sites on CO2 leakage, supporting regional safety and environmental risk management for well site leakage.